Emotional intelligence dan organizational communication terhadap teamwork effectiveness - Widiarni, Prastiwi; Nugrohoseno, Dwiarko (Jurnal Ilmu Manajemen, 2024)
This study aims to test and analyze the effect of emotional intelligence and organizational communication on teamwork effectiveness at PT X. The study employed a quantitative approach with total of 91 employees respondents and utilized saruration technique. The data were analyzed using multiple linear regression with SPSS version 25 software. Result showed that emotional intelligence predicted teamwork effectiveness, organizational communication predicted teamwork effectiveness, emotional intelligence and organizational communication jointly predicted teamwork effectiveness. The implication of this study for PT X is that companies need to improve teamwork effectiveness by creating a comfortable working atmosphere and enhancing both the emotional intelligence of employees and organizational communication